From Africa to America: Precarious Belongings in NoViolet Bulawayo’s We Need New Names - Cobo-Piñero, Rocío (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2018)
This article analyzes NoViolet Bulawayo’s critically acclaimed debut novel We Need New Names (2013), bringing to the fore the legacies of colonialism and the subsequent diaspora to the West. Like the work of other contemporary Afrodiasporic writers such as Chimamanda Ngozi Adichie, Taiye Selasi and Imbolo Mbue, Bulawayo’s narrative recreates the problematic space of dislocated, transnational migrants who are attached to a postcolonial and a metropolitan “home,” and denied fundamental rights in both. Unstable belongings are part of the new subjectivities forged in postcolonial contexts, where invisibility is also a social, political and economic sign of precarity. In Bulawayo’s novel, social conflicts, abusive governments, linguistic imposition, displacement and migration are revealed through a group of African children, first in a Zimbabwean shantytown and then in the United States. This study contextualizes the diasporic dilemmas of belonging and identity formation, while at the same time exploring the possibilities of political agency within contemporary Afrodiasporic literature. Keywords: precarious belongings; NoViolet Bulawayo; Afrodiasporic literature; postcoloniality; invisibility